A maximum power point tracking for photovoltaic systems based on Monod equation. (January 2019) - Camilo, Jones C.; Guedes, Tatiana; Fernandes, Darlan A.; Melo, J.D.; Costa, F.F.; Sguarezi Filho, Alfeu J.
Abstract: This paper presents a maximum power point tracking (MPPT) algorithm based on the Monod equation for photovoltaic (PV) systems with DC regulation. This equation is applied to estimate the power output for each current output of PV generator. The proposed MPPT permits to quickly estimate the required duty-cycle by the step-up converter that is associated with the provided maximum power from the generator. The new MPPT algorithm has a lower implementation complexity and with a lower computational effort, which is important to implement using less expensive controllers and low cost processor. The proposed algorithm is tested in a PV system composed by solar module that emulates of PV generator and which the input voltage is regulated by a push-pull converter, supplying a DC load. The experimental results demonstrate that use of the Monod equation improves the dynamics of the PV system and find the maximum value of power for conditions of low irradiance unlike other methodologies. Highlights: The MPPT algorithm based on the Monod equation is proposed. The proposal calculates the required duty-cycle by the converter to provided MPP. The mathematical formulation of the proposal has low complexity. The MPPT algorithm can be programed in low cost microcontrollers. The proposed MPPT improves the dynamics of the PV system.